PENELUSURAN KARAKTERISTIK PERILAKU KONSUMEN DENGAN METODE AUTOMATIC INTERACTION DETECTION (AID) - Rusgiyono, Agus (MEDIA STATISTIKA, 2008)
AID methods used to see relation between respons variable with a number of variable of predictor and also see related pattern between predictors. In AID procedures data disjointed in two group determined by variable of predictor most explaining of difference  values of respons variables, and this recuring process so that yielded to with refer to splits in data. Every split yield new data sub which its variable values is mutually and exclusive  exhaustive. Its end results  with refer toing crotch is so-called tree of AID   Keywords : split, tree of AID